Adab-Centric Pedagogy and Tarbiyah: A Comprehensive Analysis of Their Impact on Islamic Education System in South India - Mohamed Iyas Valarthodi; Abubaker Barry; Mahasri Shobahiya; Abdul Hafeez VM; Ameen KC (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the integration and effectiveness of adab-centric pedagogy and tarbiyah within South India's Islamic education system, particularly focusing on Kerala's educational institutions. Through a mixed-methods approach combining qualitative interviews, quantitative surveys, and longitudinal data analysis across 15 major Islamic educational institutions, the research investigates how traditional Islamic educational principles are effectively merged with modern pedagogical approaches. The study employed the Comprehensive Islamic Education Assessment Framework (CIEAF) and Multi-Dimensional Character Assessment Protocol (MDCAP) to evaluate both academic and character development outcomes. Results demonstrate significant improvements in student performance, including a 45% enhancement in character development metrics and a 27% increase in academic achievement. The findings establish that the successful integration of adab-centric pedagogy and tarbiyah principles creates a robust educational model that effectively balances traditional Islamic values with contemporary educational requirements.